Effect of moringa leaf powder supplementation on performance and antioxidant activity in broilers under heat stress: Moringa Leaf Powder Supplementation in Broilers under Heat Stress - VEDENDER .G P; VENKATESWARLU .M; NAGALAKSHMI .D; HARIKRISHNA .CH; PARASHURAMULU .S (Indian Journal of Poultry Science, 2025)
An experiment was conducted to investigate the effect of Moringa leaf powder supplementation on performance and antioxidant activity to alleviate heat stress in broilers during summer months. The experiment was conducted on 240 broiler chicks (Cobb-300) and randomly categorized into six dietary treatment groups with 8 replicates with 5 birds in each replicate (6×8×5). A corn-soy basal diet (BD) was prepared as a control and BD supplemented with chlortetracycline at 0.05% (BD-C), vitamin E at 0.025% (BD-E) and Moringa oleifera leaf powder (MLP) at 0.25% (BD-MLP-0.25), 0.5% (BD-MLP-0.5) and 0.75% (BD-MLP-0.75) of BD were prepared. MLP supplementation at 0.5% and 0.75% levels significantly improved (P